Knowing KUR Perception: With An Islamic Financial Behavior Approach And Digital Financial Inclusion As An Intervening Variable In MSME Tasikmalaya, Indonesia - Nita Fauziah Oktaviani; Evilia Sri Yuniar; Barin Barlian; Irly Artiara Irawan (Journal of International Conference Proceedings, 2024)
This research was to find out how Islamic financial behavior influences perceptions of KUR and also digital financial inclusion as an intervening variable. KUR (People's Business Credit) is a financing program provided to MSMEs as a form of support from the Indonesian government.  KUR is credit given to MSMEs that are not yet bankable but have potential for working capital and investment purposes. However, the number of MSMEs using KUR is still below the Indonesian government's target. The research used mixed method  with a sample size of 150 respondents consisting of MSMEs in Tasikmalaya. The research results show that Islamic Financial Behavior has a significant influence on the perception of KUR, Islamic Financial Behavior has a significant influence on Digital Financial Inclusion and Islamic Financial through Digital Financial Inclusion has a significant influence on the perception of KUR in Tasikmalaya MSMEs. This shows that the Government must be able to increase digital financial inclusion and have some sharia-based KUR concept.